2018
DOI: 10.1242/jeb.173864
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone implants make stress hyporesponsive birds

Abstract: In birds, the use of corticosterone (Cort) implants is a frequent tool aimed at simulating systemic elevations of this hormone and studying effects on biological traits (e.g. physiology, morphology, behavior). This manipulation may alter adrenocortical function, potentially changing both baseline (Cort) and stress-induced (Cort) plasma Cort levels. However, implant effects on the latter trait are rarely measured, disregarding downstream consequences of potentially altered stress responses. Here, we analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…We show that elevation of plasma cortisol concentrations within the physiological range for 1-2 weeks had profound effects on measures of HPA axis reactivity and CBG concentrations. This is similar to the results of Torres-Medina et al (2018) that showed that treatment with corticosterone implants can also cause reduced corticosterone levels in response to capture and handling. However, our study took the result from Torres-Medina et al (2018) one step further as we showed how treatment with exogenous GCs suppresses CBG concentrations and we also investigated the possibility of fitness consequences of reduced HPA axis reactivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We show that elevation of plasma cortisol concentrations within the physiological range for 1-2 weeks had profound effects on measures of HPA axis reactivity and CBG concentrations. This is similar to the results of Torres-Medina et al (2018) that showed that treatment with corticosterone implants can also cause reduced corticosterone levels in response to capture and handling. However, our study took the result from Torres-Medina et al (2018) one step further as we showed how treatment with exogenous GCs suppresses CBG concentrations and we also investigated the possibility of fitness consequences of reduced HPA axis reactivity.…”
Section: Discussionsupporting
confidence: 90%
“…Although these issues were highlighted 10-15 years ago (Romero, 2004;Fusani, 2008; see also Sopinka et al 2015;Crossin et al, 2016), detailed studies about the potential complications of manipulating hormones in wild animals have not been widely performed except in birds. Torres-Medina et al (2018) reviewed the consequences of experimentally elevated GCs on baseline and stress-induced corticosterone levels from previous studies on multiple bird species that were published 2005-2015. Many but not all of these studies were conducted in free-living birds.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the results of Torres-Medina et al (2018) that showed that treatment with corticosterone implants can also cause reduced corticosterone levels in response to capture and handling. However, our study took the result from Torres-Medina et al (2018) one step further as we showed how treatment with exogenous GCs suppresses CBG concentrations and we also investigated the possibility of fitness consequences of reduced HPA axis reactivity. Despite these observed shifts in the functionality of the neuroendocrine stress axis and the sustained elevations in GCs, we found no change in body mass or offspring and adult survival.…”
Section: Discussionsupporting
confidence: 90%
“…When it is feasible, daily supplementation may be effective in maintaining sustained elevations in hormone concentrations and provide an alternative to other methods like implants that carry some disadvantages (Sopinka et al, 2015). For example, Torres-Medina et al (2018) showed that silastic implants, time release pellets, or osmotic pumps that contain corticosterone can also suppress the responsiveness of the HPA axis in birds, which could decrease overall exposure to circulating corticosterone. Our study shows that even regular provisioning of exogenous GCs rather than implants, such as through food in our study (see also Dantzer et al, 2017) or through other methods (Vitousek et al 2018), may also decrease the activity of the HPA axis and cause a reduced ability to mount an increase in circulating GCs in response to an environmental challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Across species, silastic implants have been successfully used to raise CORT levels for anywhere from a few days ( Astheimer et al, 2000 ; Hayward and Wingfield, 2004 ; Criscuolo et al, 2005 ; Martin et al, 2005 ; Angelier et al, 2007 ) to 3 weeks post-implantation in vivo ( Ouyang et al, 2013 ) and in vitro ( Newman et al, 2010 ). However, the use of implants to raise CORT levels has not been consistently successful ( Crossin et al, 2012 ; Ouyang et al, 2013 ; Hau and Goymann, 2015 ; Lattin et al, 2016 ; Torres-Medina et al, 2018 ). Although the implants used in our study may have failed to release CORT, this seems unlikely given that in vitro studies have shown that CORT continues to be released across the membrane over 4 weeks ( Newman et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%